Subjective and objective needs analysis of Mandarin learners - Lam, Kai Chee; Ang, Lay Hoon; Hoe, Foo Terng; Ting, Hie Ling (SAGE Publications, 2023)
Needs analysis for language courses has to be carried out continuously to keep up with global changes and the needs of learners. This mixed-method study aims to describe the subjective and objective needs of the Mandarin learners in Universiti Malaysia Sarawak (UNIMAS), Malaysia, and to check if these needs correspond with each other. Targetting at 120 learners and two instructors, a questionnaire survey was distributed, and complemented by qualitative data derived from focus group interviews. Result shows that learners’ subjective needs correspond with objective needs for motivational orientation, textbook, and cultural exposure. Statistically insignificant differences were found in the expected skills to learn, lecture-activities ratio, and teaching-learning activities. The study concludes that flexibility, student-centeredness and practicality are elements to look into for course improvement. Future research can explore learners’ needs in mastering writing skill, as well as the needs differences among learners across different levels. The study complements the understanding and knowledge of needs analysis in regard to Mandarin learning outside of China.